2021
DOI: 10.3390/ijms221910368
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin and Its New Derivatives: Correlation between Cytotoxicity against Breast Cancer Cell Lines, Degradation of PTP1B Phosphatase and ROS Generation

Abstract: Breast cancer is the most common cancer of women—it affects more than 2 million women worldwide. PTP1B phosphatase can be one of the possible targets for new drugs in breast cancer therapy. In this paper, we present new curcumin derivatives featuring a 4-piperidone ring as PTP1B inhibitors and ROS inducers. We performed cytotoxicity analysis for twelve curcumin derivatives against breast cancer MCF-7 and MDA-MB-231 cell lines and the human keratinocyte HaCaT cell line. Furthermore, because curcumin is a known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 58 publications
(86 reference statements)
0
4
0
Order By: Relevance
“…PTP1B was conventionally considered a routine treatment for diabetes [32] and obesity originally [33]. Recently, it has been considered as a therapeutic objective in other fields including tumors [34], neuroinflammation [10], vascular endothelium protection [35], and neuroprotection. Many researches have revealed that the PTP1B gene is exceedingly expressed in ovarian cancer, gastric cancer, prostate cancer, and breast cancer and is related to poor prognosis [36].…”
Section: Discussionmentioning
confidence: 99%
“…PTP1B was conventionally considered a routine treatment for diabetes [32] and obesity originally [33]. Recently, it has been considered as a therapeutic objective in other fields including tumors [34], neuroinflammation [10], vascular endothelium protection [35], and neuroprotection. Many researches have revealed that the PTP1B gene is exceedingly expressed in ovarian cancer, gastric cancer, prostate cancer, and breast cancer and is related to poor prognosis [36].…”
Section: Discussionmentioning
confidence: 99%
“…This is seemingly associated to differences in the structure of these compounds. CUR suppress p300-HAT activity and reportedly inhibits cardiomyocyte hypertrophy and the development of heart failure [23]. In addition, there have been extensive structure-activity studies on the natural product CUR, and studies targeting p300-HAT activity and cardiomyocyte hypertrophy have been carried out [9].…”
Section: Discussionmentioning
confidence: 99%
“…CUR, with many bioactivities, has attracted worldwide attention. In addition, many derivatives of CUR have been synthesized using CUR as a lead compound and are being actively investigated [22,23]. However, little research has been conducted on the structure-activity relationship of CUR using cardiomyocyte hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research study reported that curcumin had affected the enzyme PTP1B by increasing the sensitivity of hepatic leptin and insulin of rat liver [14,15]. Curcumin also inhibited PTP1B enzyme action that leads to improve hepatic leptin and insulin signaling in rats fed with fructose [16][17][18][19][20]. In addition, curcumin remarkably reduced the podocyte injury and proteinuria induced by fructose, the expression of PTP1B, and cut down the activity of insulin receptor and insulin receptor substrate 1 of fructose-fed rats [21].…”
Section: Introductionmentioning
confidence: 98%